Tris-(8-hydroxyquinoline) aluminium thin film as saturable absorber for passively Q-switched erbium-doped fibre laser - Salam, Sameer; Harun, Sulaiman Wadi; Al-Masoodi, Ahmad H.H.; Ahmed, Mahmoud Hazzaa M.; Al-Masoodi, Ab H.H.; Alani, Ibrahim A.M.; Abd Majid, Wan Haliza; Wong, Wei Ru; Yasin, Moh (Institution of Engineering and Technology (IET), 2019)
A passively Q-switched erbium-doped fibre laser was demonstrated by using tris-(8-hydroxyquinoline)aluminium (Alq3) organic material as a passive saturable absorber (SA). The SA was fabricated by a drop casting technique at room temperature and incorporated into a laser cavity by inserting it between two optical fibre ferrules. The Q-switched fibre laser operates at a centre wavelength of 1559 nm with a full-width half maximum of 1 nm. The generated pulse train is stable and has a pulse width decreased from 6.65 to 1.2 μs and the pulse repetition rate increased from 31.65 to 144.5 kHz as the pump power increased from 20 to 122 mW. The maximum pulse energy obtained is 63.89 nJ. This work indicates that the Alq3 as SA has a great potential to be utilised for pulsed laser generation. To the best of the authors' knowledge, this is the first time an organic material is utilised as a SA device for generating a stable Q-switched laser pulse. © 2019 Institution of Engineering and Technology. All rights reserved.